A Typology of Family Firms: An Investigation of Entrepreneurial Orientation and Performance. (June 2019) - Stanley, Laura J.; Hernández-Linares, Remedios; López-Fernández, María Concepción; Kellermanns, Franz W.
Drawing on family firm heterogeneity research, we develop a typology of family firms using differences in family influence and firm life cycle. We offer hypotheses regarding the relationships between the different firm types and two important outcomes: Entrepreneurial orientation (EO) and performance. Applying latent profile analysis to a sample of 684 Spanish and Portuguese family firms using variables related to family influence (i.e., ownership, family CEO) and firm life cycle (i.e., generational management, size, and presence of board of directors), we find four family firm types, which differentially affect EO and performance. Implications of our findings for EO, family firm performance, and the development of family firm typologies are discussed.